KOMUNITAS 234 SC DI PEKANBARU (STUDI TENTANG KELOMPOK SOSIAL) - Kiki Melia Sari; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study, entitled Community 234 sc in Pekanbaru (Studies Social Group).Researchers interested in this theme because the researchers wanted to see whatmakes a person interested to enter this community, how its characteristics, whatmotivation, and the impact of joining this community, both positive and negative.To know the results of this study, the authors used data collection techniquesby using observation, interviews and questionnaires with respondents. As for howsampling researchers do simple random sampling technique, where the determinationof the respondents through simple random sampling with the number of respondents78 people of 150 members who are still active in the community. The theory used inthis research is the theory of social groups, the research method used is descriptivequantitative.The results of this study indicate that the nature of the 234 SC in Pekanbarucommunity members to follow this community aims to strengthen kinship though notby blood but more than you, can channel the feelings and opinions in the community.Community 234 SC has a positive impact on its members, the impact is a memberhaving an opportunity to gain social relations in the world of work, as well asentrepreneurship and have a sense of solidarity.The results of this study are expected to provide a general overview to allthose who need information about Community 234 SC in Pekanbaru.Keywords: Social groups, Community 234 SC Pekanbaru.